Task-dependent frequency of intermuscular coherence in the presence of transcutaneous electrical spinal cord stimulation: a feasibility study - McNicol, Emily Lynn; Osuagwu, Bethel; Vučković, Aleksandra (Frontiers in Human Neuroscience, 2025)
The task-dependent frequency of common neural drive to muscles has important applications for motor rehabilitation therapies. While it is well established that muscle dynamics influence the synchronicity of neural drive, the modulation of this coherence between static and dynamic movements remains unclear. Transcutaneous electrical spinal cord stimulation (TESCS) is believed to enhance spinal cord excitability, potentially improving brain-muscle communication; however, its effect on common neural drive to muscles has not yet been reported. This study aimed to investigate differences in intermuscular coherence (IMC) frequency between static and dynamic movement tasks and determine whether it is feasible to enhance it by TESCS. Participants performed static and dynamic hand grip tasks at different timepoints with respect to stimulation, set to 80% tolerable intensity. Surface EMG signals were recorded from the flexor digitorum superficialis (FDS) and extensor digitorum communis (EDC) muscles during each trial to determine beta- (15–30 Hz) and gamma- (30–48 Hz) band intermuscular coherence. The sum of IMC (IMCarea) was significantly greater (pB = 0.018, pD = 0.0183, pIM = 0.0172, p5 = 0.0206, p10 = 0.0183, p15 = 0.0172) in the gamma-band for the dynamic task compared to the static task at every timepoint (before TESCS, during TESCS and immediately, 5-min, 10-min, and 15-min after TESCS) which may reflect a mechanism of increased efficiency of corticospinal interactions and could have implications for the types of movements that should be performed while receiving TESCS. There was no immediate measurable effect of TESCS on IMCarea at any timepoint in the beta-band (p = 0.25, p = 0.31) or gamma-band (p = 0.52, p = 0.73) for either the static or dynamic task respectively. This could be explained by corticospinal networks already working at maximum capacity in able-bodied individuals or that a longer duration of TESCS is required to elicit a measurable effect. While the intra-task difference in beta- and gamma-band IMCarea between static and dynamic tasks was statistically significant (pIM = 0.0275, p5 = 0.0275, p15 = 0.0031) at timepoints after stimulation, we did not find direct evidence that TESCS influenced this beta-gamma interaction. Thus, further investigation is needed to establish any causal relationship.